A new genus and new species of Paguridae (Crustacea: Decapoda: Anomura) from shallow subtidal waters in Okinawa Island, the Ryukyu Islands, Japan - Komai, Tomoyuki (Zootaxa, 2015)
During a survey on decapod crustacean fauna of shallow coral reefs and nearby environments in Okinawa Island, Ryukyu Archipelago, Japan, four specimens of a small but distinctive undescribed species of pagurid hermit crab, which could not be referred to any known genus, were collected. The new taxon, Eutrichopagurus shirakawai n. gen., n. sp., is described and illustrated herein. The new genus is characterized by the possession of 11 pairs of deeply quadriserial phyllobranchiate gills, the third maxilliped with well-developed crista dentata and one or two accessory teeth on the ischium, the presence of unpaired left gonopore in the female, the absence of paired first pleopods in the female, and the telson with prominent tuft of setae on the lateral margin of the posterior lobes; the male is unknown at present. It appears close to Trichopagurus de Saint Laurent, 1968, but the deeply quadriserial gills immediately distinguish Eutrichopagurus from Trichopagurus. The new genus is also compared with other genera characterized by the possession of 11 pairs of quadriserial phyllobranchiate gills and the lack of paired first pleopods in females.